2020
DOI: 10.1210/clinem/dgaa803
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Metabolic Profiling of a Novel Human Gut-derived LEAP2 Fragment

Abstract: Context The mechanisms underlying Roux-en-Y gastric bypass (RYGB) surgery-induced weight loss and the immediate postoperative beneficial metabolic effects associated with the operation remain uncertain. Enteroendocrine cell (EEC) secretory function has been proposed as a key factor in the marked metabolic benefits from RYGB surgery. Objective To identify novel gut-derived peptides with therapeutic potential in obesity and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 51 publications
5
48
1
Order By: Relevance
“…It may also yield understanding potential targets of interest (eg, dipeptidyl peptidase-4 inhibitors and incretins) for health. Another point raised by the present work ( 6 ) is whether or not LEAP2 can affect human physiology independent of GHSR. For instance, a consideration of these bariatric and in vitro findings is the influence of physical activity on gut hormones.…”
Section: Invited Commentarymentioning
confidence: 85%
See 2 more Smart Citations
“…It may also yield understanding potential targets of interest (eg, dipeptidyl peptidase-4 inhibitors and incretins) for health. Another point raised by the present work ( 6 ) is whether or not LEAP2 can affect human physiology independent of GHSR. For instance, a consideration of these bariatric and in vitro findings is the influence of physical activity on gut hormones.…”
Section: Invited Commentarymentioning
confidence: 85%
“…Novel work presented in this issue of the Journal of Clinical Endocrinology & Metabolism demonstrates the impact of RYGB on genome-wide expression patterns in enteroendocrine cells from human gut biopsies during and after surgery in patients with obesity and/or diabetes ( 6 ). Liver-expressed antimicrobial peptide 2 (LEAP2) mRNA in particular was upregulated from gut biopsies, while circulating fasting and postprandial plasma levels were unchanged.…”
Section: Invited Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed proLEAP2 processing enzyme is furin, a calcium-dependent serine endoprotease that cleaves peptides at the C-terminal end of paired basic residues and usually processes precursors in the constitutive secretory pathway [50]. A recent study found that LEAP2 is also processed into LEAP2 [38][39][40][41][42][43][44][45][46][47] in the intestinal epithelium of humans and mice [51]. LEAP2's amino acid sequence is highly conserved in mammals, particularly the N-terminal end, where the initial six residues are identical across species [52,53].…”
Section: Biosynthesismentioning
confidence: 99%
“…LEAP2 suppressed food intake and growth hormone release and maintained viable glucose levels during chronic caloric restriction in mice (Ge et al., 2018). The six N‐terminal amino acids of LEAP2 are crucial for GHSR1a binding, and its 10‐amino‐acid N‐terminal fragment stimulated insulin release from human pancreatic islets (Hagemann et al., 2020; Wang et al., 2019). Plasma LEAP2 concentrations in humans increased with body weight gain and elevations of blood glucose and decreased with fasting and weight loss surgery (Mani et al., 2019).…”
Section: Introductionmentioning
confidence: 99%